PTU-041 Thromboelastography demonstrates a hypercoagulable profile in cirrhosis and correlates with liver disease severity. (June 2019) - Zakeri, Nekisa; Prat, Laura Iogna; Patch, David; Yu, Dominic; Majumdar, Avik; Melikian, Clare; Tsochatzis, Emmanuel
Abstract : Introduction: Recent literature supports the paradigm of a rebalanced, although fragile, haemostasis equilibrium in compensated cirrhosis, poorly reflected by standard coagulation tests. We performed thromboelastography (TEG) to evaluate the global haemostatic profile of patients with stable decompensated cirrhosis, assessing for correlation with liver disease severity. We examined whether portal venous blood displayed an increased pro-thrombotic profile in comparison to peripheral and hepatic venous blood, potentially contributing to the high incidence of portal venous thrombosis in cirrhosis. Methods: 18 cirrhotic patients undergoing transjugular intrahepatic portosystemic shunt procedures for refractory ascites or previous variceal bleeding were prospectively studied. Exclusion criteria included recent anticoagulation, infection or variceal bleeding (within two weeks), haematological disorders, or splanchnic venous thrombosis. Reaction time (R), kinetic time (K), alpha-angle, and maximum amplitude (MA) were measured in citrated portal, hepatic and peripheral venous blood using TEG Haemostasis Analyser 5000. Correlations were assessed with platelet count, prothrombin time (PT), international normalised ratio (INR), activated partial thromboplastin time (APTT), fibrinogen concentration; and evaluated against liver disease severity scores. Statistical analysis was performed using SPSSv24. Results: Patients were predominantly male (61%), with Child Pugh B cirrhosis (89%), mean MELD score 11.6±3.6. A frequent hypercoagulable profile was demonstrated (shortened R-time in 89% of patients, shortened K-time in 69%, increased alpha-angle in 81%), despite a prolonged INR, PT, APTT in 56–61% of patients. R-time (reflecting soluble clotting factors concentration) did not significantly correlate with INR or PT. MA (associated with platelet number/function) was normal in 83% of patients, despite thrombocytopenia present in 56%. Portal venous blood displayed a comparable TEG profile to peripheral and hepatic venous blood. The MA parameter of TEG demonstrated the strongest correlation with UKELD (r=-0.7, p=0.001) and MELD (r=-0.6, p=0.02) scores. Conclusion: Our cohort of decompensated cirrhotic patients displayed an overall hypercoagulable TEG profile, despite co-existing thrombocytopenia and a prolonged INR, PT and APTT, demonstrating poor representation of the global haemostatic profile by standard coagulation tests. TEG in peripheral venous blood accurately reflected the haemostatic profile of portal venous blood. TEG parameters correlated with liver disease severity scores in spite of poor representation by INR within these scores, thus the potential benefit of utilising TEG for liver disease severity assessment in routine clinical practice warrants further evaluation.